The Aβ protofibril selective antibody mAb158 prevents accumulation of Aβ in astrocytes and rescues neurons from Aβ-induced cell death - Sofia Söllvander; Elisabeth Nikitidou; Linn Gallasch; Marlena Zyśk; Linda Söderberg; Dag Sehlin; Lars Lannfelt; Anna Erlandsson (Journal of Neuroinflammation, 2018)
Abstract Background Currently, several amyloid beta (Aβ) antibodies, including the protofibril selective antibody BAN2401, are in clinical trials. The murine version of BAN2401, mAb158, has previously been shown to lower the levels of pathogenic Aβ and prevent Aβ deposition in animal models of Alzheimer’s disease (AD). However, the cellular mechanisms of the antibody’s action remain unknown. We have recently shown that astrocytes effectively engulf Aβ42 protofibrils, but store rather than degrade the ingested Aβ aggregates. In a co-culture set-up, the incomplete degradation of Aβ42 protofibrils by astrocytes results in increased neuronal cell death, due to the release of extracellular vesicles, containing N-truncated, neurotoxic Aβ. Methods The aim of the present study was to investigate if the accumulation of Aβ in astrocytes can be affected by the Aβ protofibril selective antibody mAb158. Co-cultures of astrocytes, neurons, and oligodendrocytes, derived from embryonic mouse cortex, were exposed to Aβ42 protofibrils in the presence or absence of mAb158. Results Our results demonstrate that the presence of mAb158 almost abolished Aβ accumulation in astrocytes. Consequently, mAb158 treatment rescued neurons from Aβ-induced cell death. Conclusion Based on these findings, we conclude that astrocytes may play a central mechanistic role in anti-Aβ immunotherapy.